Association of hand grip muscle strength and endurance with pulmonary function tests in healthy young adults - Jolly Bhattacharjya (Wolters Kluwer Medknow Publications, 2022)
Introduction: Modern society is creating a severe threat to the health. Such as physical inactivity leading to muscle weakness, air pollution causing respiratory distress etc. But the relationship between hand grip muscle strength (HGS) and pulmonary function is not clear. Hence, the present study was designed to investigate is there any association of handgrip muscle strength and endurance with pulmonary function test (PFT) parameters in healthy young adults. Materials and Methods: In this cross-sectional study, 80 healthy volunteers of 18-21 years of age had participated. PFT was done using portable spirometer. For measurement of muscle strength and endurance, handgrip dynamometer was used. Statistical analysis was done using SPSS 26 software. Mean was calculated for the general characteristics. Pearson correlation coefficient was calculated to analyze the association of handgrip muscle strength and various indices of pulmonary function. Results: In this study (47), 58.8% were male and (33) 41.3% were female. Muscle strength, endurance, forced vital capacity (FVC), forced expiratory flow in 1 s (FEV1), peak expiratory flow rate (PEFR) were significantly higher in males than females. There were significantly positive correlation of handgrip muscle strength with FVC (r = 0.522**, P = 0.000) and FEV1 (r = 0.486**, P = 0.000). Muscle endurance was significantly positively correlated with FVC (r = 0.397**, P = 0.000), FEV1 (r = 0.438**, P = 0.000) and PEFR (r = 0.221*, P = 0.049). Conclusions: Hence, it can be concluded that there is a positive correlation of handgrip muscle strength and endurance with pulmonary function. Hence, HGS can also be used to predict pulmonary function.